Considerations for Clinical Trials of Staphylococcus aureus Bloodstream Infection in Adults. (10th September 2018) - Holland, Thomas L; Chambers, Henry F; Boucher, Helen W; Corey, G Ralph; Coleman, Rebecca; Castaneda-Ruiz, Bibiana; Fowler, Vance G
Abstract: Clinical trials for Staphylococcus aureus bloodstream infections (SAB) are broadly grouped into 2 categories: registrational trials intended to support regulatory approval of antibiotics for the treatment of SAB and strategy trials intended to inform clinicians on the best treatment options for SAB among existing antibiotics. Both types of SAB trials are urgently needed but have been limited by cost, complexity, and regulatory uncertainty. Here, we review key SAB trial design considerations for investigators, sponsors, and regulators. Abstract : Design of clinical trials for Staphylococcus aureus bacteremia is challenging. In the absence of a consensus, there has been substantial heterogeneity in enrolled participants, comparator agents, and endpoints. Recommendations for consistent trial design are provided.